Characterization of low-frequency inter-ELM modes of H-mode discharges at ASDEX Upgrade. (3rd October 2018) - Vanovac, B.; Wolfrum, E.; Hoelzl, M.; Willensdorfer, M.; Cavedon, M.; Harrer, G.F.; Mink, F.; Denk, S.S.; Freethy, S.; Dunne, M.; Manz, P.; Luhmann, N.C.
Abstract: The steep edge gradient region of tokamak plasmas in the high confinement regime is known to drive instabilities, which cause transport. Several diagnostics are used to allow for a high degree of characterization of low-frequency modes appearing in between type-I edge localizes modes (ELMs). These modes are dominantly observed in electron cyclotron emission (ECE) and ECE imaging measurements as a modulation of radiation temperature ( ). In the radial magnetic field ( measurements, the frequency range of 4 kHz to 12 kHz is observed. The position of the mode is determined to be at the upper part of the steep gradient region, the poloidal mode velocity is changing from 1.5  ±  0.5 km s −1 to 2.5  ±  0.5 km s −1 and the toroidal mode number is 13 to 14. A comparison with the measured velocity leads to the conclusion that the phase velocity of the mode is smaller than 3 km s −1 or zero. The poloidal structure of the modes is found to agree with the poloidal structure size associated with n   =  13 as estimated from the equilibrium calculations. The modes are compared between two different heating phases during one discharge, and are found to differ in duration, velocity, frequency and toroidal mode number. The possibility of non-linear interaction between these modes and other, high frequency modes existing in the narrow pedestal, is assessed via bicoherence analysis. The presented analysis gives an unprecedented picture of the mode, its position, its structure and its velocity, calling for comparison with non-linear modelling.